The Theban plays of Sophocles - Sophocles (Yale new classics., 2007)
In this needed and highly anticipated new translation of the Theban plays of Sophocles, David Slavitt presents a fluid, accessible, and modern version for both newcomers to the plays and established admirers. Unpretentious and direct, Slavitt's translation preserves the innate verve and energy of the dramas, engaging the reader or audience member directly with Sophocles' great texts. Slavitt chooses to present the plays not in narrative sequence but in the order in which they were composed: "Antigone", "Oedipus Tyrannos", "Oedipus at Colonus"; he thereby underscores the fact that the story of "Oedipus" is one to which Sophocles returned over the course of his lifetime. This arrangement also lays bare the record of Sophocles' intellectual and artistic development. Renowned as a poet and translator, Slavitt has translated Ovid, Virgil, Aeschylus, Aristophanes, Ausonius, Prudentius, Valerius Flaccus, and Bacchylides as well as works in French, Spanish, Portuguese, and Hebrew. In this volume, he avoids personal intrusion on the texts and relies upon the theatrical machinery of the plays themselves. The result is a major contribution to the art of translation and a version of the Oedipus plays that will appeal enormously to readers, theatre directors, and actors.